#### Answer

$= \frac{-(4x-3)}{(5x+1)}$

#### Work Step by Step

$\frac{(4x-3)(7-2x)}{(2x-7)(5x+1)}$
$= \frac{(4x-3)(-(2x-7))}{(2x-7)(5x+1)}$
$= \frac{-(4x-3)}{(5x+1)}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$= \frac{-(4x-3)}{(5x+1)}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.